2008
DOI: 10.1007/s00213-008-1404-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic and intra-nucleus accumbens 5-HT2C receptor compounds on ventral tegmental area self-stimulation thresholds in rats

Abstract: These results suggest that 5-HT(2C) receptors play an inhibitory role in regulating reward-related behaviour while 5-HT(2C) receptor activation in the NAc shell did not appear to influence VTA ICSS behaviour under the present experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 92 publications
3
29
1
Order By: Relevance
“…Considerable evidence also shows that 5-HT 2C receptor agonists reduce responding for a variety of other rewards, including nicotine, cocaine and brain stimulation reward Cunningham et al 2011;Hayes et al 2009;Katsidoni et al 2011), which might indicate that the antiobesity effect of lorcaserin (and other 5-HT 2C agonists) may be achieved by altering motivation for hedonic aspects of food which can drive overeating in some individuals (Kenny 2011;Berthoud 2011). Given the complexity and redundancy of systems that regulate feeding behaviour, energy expenditure and weight control, it is likely that drugs with multiple modes of action are most likely to produce a therapeutic benefit (Kennett and Clifton 2010;Powell et al 2011;Betley et al 2013;Heal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable evidence also shows that 5-HT 2C receptor agonists reduce responding for a variety of other rewards, including nicotine, cocaine and brain stimulation reward Cunningham et al 2011;Hayes et al 2009;Katsidoni et al 2011), which might indicate that the antiobesity effect of lorcaserin (and other 5-HT 2C agonists) may be achieved by altering motivation for hedonic aspects of food which can drive overeating in some individuals (Kenny 2011;Berthoud 2011). Given the complexity and redundancy of systems that regulate feeding behaviour, energy expenditure and weight control, it is likely that drugs with multiple modes of action are most likely to produce a therapeutic benefit (Kennett and Clifton 2010;Powell et al 2011;Betley et al 2013;Heal et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A second line of preclinical evidence supports a role for 5-HT 2C receptors to influence motivation for a variety of rewarding stimuli. Thus, doses of 5-HT 2C receptor agonists that reduce food intake also reduce responding for cocaine, nicotine and ethanol Cunningham et al 2011) and elevate thresholds for intracranial self-stimulation (ICSS) (Hayes et al 2009;Katsidoni et al 2011;Zeeb et al 2015). These effects may involve altered dopaminergic function since 5-HT 2C receptors exert a powerful regulatory influence over DA mesolimbic tone, with 5-HT 2C agonists reliably decreasing VTA cell firing and DA release within the n. accumbens (Di Matteo et al 2002;Berg et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Our result with R-96544 is in accordance with a study by Benaliouad and colleagues (2007), in which the selective 5-HT 2A receptor antagonist M-100907 did not affect brain stimulation reward. Recently, it was demonstrated that the selective 5-HT 2C receptor agonist WAY-161503 significantly increased ICSS thresholds, whereas the selective 5-HT 2C receptor antagonist SB-242084 did not affect brain stimulation reward (Hayes et al 2009a). Our results are consistent with the latter findings but contradict the prevailing view that 5-HT 2A and 5-HT 2C receptor stimulation induces opposite behavioral, neurophysiological, and neurochemical effects Muller and Huston 2006).…”
Section: Discussionmentioning
confidence: 99%
“…ICSS is generally not affected or only depressed by systemically administered agonists and/or antagonists for 5HT 1 receptors (Harrison et al, 1999;Harrison and Markou, 2001), 5HT 2 receptors (Benaliouad et al, 2007;Hayes et al, 2009;Katsidoni et al, 2011), 5HT 3 receptors (Greenshaw, 1993;Hatcher et al, 1995), and 5HT 4 receptors (Reavill et al, 1998) (see Hayes and Greenshaw, 2011 for review). An exception is that low doses of the 5HT 1A agonist 8-OH-DPAT may facilitate ICSS (Harrison and Markou, 2001).…”
Section: Icss In Abuse Potential Testingmentioning
confidence: 99%